KEMANDIRIAN DAN PEMBERDAYAAN EKONOMI BERBASIS PESANTREN (Studi atas Peran Pondok Pesantren Al-Ittifaq Kecamatan Rancabali Kabupaten Bandung terhadap Kemandirian Eknomi Santri dan Pemberdayaan Ekonomi Masyarakat Sekitarnya) - Rizal Muttaqin (JESI (Jurnal Ekonomi Syariah Indonesia), 2011)
Research is aimed to criticize the coaching model of students economic autonomy and community economic empowerment, the relationship between spirituality motivation and kyai leadership with students economic autonomy and relationship coaching that carried out by the pesantren with community economic empowerment. The data are analyzed by descriptive-phenomenological analisys, Rank’s Spearman and Kendall Tau correlation analysis. This study generated four conclusions. First, the model of students economic autonomy and community economic empowerment that performed by pesantren Al-Ittifaq. Second, based on Rank’s Spearman correlation analisys and Kendall Tau correlation analisys can be concluded that there was a positive and significant correlation between the spiritual motivation (creed motivation, worship motivation and muamalah motivation) with variable of students economic autonomy. It is mean, if the spiritual motivation of students is high, then the level of economic autonomy will be the higher. Third, the results of Rank’s Spearman and Kendall Tau correlation analysis also prove that there was a positive and significant correlation between kyai leadership variables with students economic autonomy variables. That is, kyai leadership very influential in the formation of the economic autonomy of students. Fourth, by using analysis of Rank’s Spearman and Kendall Tau, there is a positive relationship between coaching variables with community economic empowerment variables. It is mean, coaching have a positive impact to economic empowerment of communities.Key word:           Pesantren, Spirituality, Kyai Leadership, Economic Autonomy, Community Economic Empowerment.